AFM study of the epitaxial growth of brushite (CaHPO4 2H2O) on gypsum cleavage surfaces - Pinto, A.; Ruiz-Agudo, E.; Putnis, Christine; Putnis, Andrew; Jiménez, A.; Prieto, M. (Mineralogical Society of America, 2010)
The epitaxial overgrowth of brushite (CaHPO4·2H 2O) by the interaction of phosphate-bearing, slightly acidic, aqueous solutions with gypsum (CaSO4·2H2O) was investigated in situ using atomic force microscopy (AFM). Brushite growth nuclei were not observed to form on the {010} gypsum cleavage surface, but instead formed in areas of high dissolution, laterally attached to gypsum [101] step edges. During the brushite overgrowth the structural relationships between brushite (Aa) and gypsum (A2/a) result in several phenomena, including the development of induced twofold twining, habit polarity, and topographic effects due to coalescence of like-oriented crystals. The observed brushite growth is markedly anisotropic, with the growth rate along the main periodic bond chains (PBCs) in the brushite structure increasing in the order [101] > [101] > [010], leading to tabular forms elongated on [101]. Such a growth habit may result from the stabilization of the polar [101] direction of brushite due to changes in hydration of calcium ions induced by the presence of sulfate in solution, which is consistent with the stabilization of the gypsum [101] steps during dissolution in the presence of HPO2-4 ions. The coupling between growth and dissolution was found to result in growth rate fluctuations controlled by the changes in the solution composition.